2020
DOI: 10.1002/ange.202009467
|View full text |Cite
|
Sign up to set email alerts
|

Co‐crystal Prediction by Artificial Neural Networks**

Abstract: As ignificant amount of attention has been given to the design and synthesis of co-crystals by both industry and academia because of its potential to change am olecules physicochemical properties.Y et, difficulties arise when searching for adequate combinations of molecules (or coformers) to form co-crystals,h ampering the efficient exploration of the targetss olid-state landscape.T his paper reports on the application of ad ata-driven co-crystal prediction method based on two types of artificial neural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…Machine learning-based models with high accuracy are typically trained by experimentally constructing an in-house negative data set for a certain type of compound, and thus have a narrow applicability domain. By constructing comprehensive negative samples via a randomly chosen approach or other computational methods, recent studies have begun to overcome this drawback . The generated negative samples would inevitably contain potential cocrystals that have not been observed, which might affect the accuracy of the predictive models.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning-based models with high accuracy are typically trained by experimentally constructing an in-house negative data set for a certain type of compound, and thus have a narrow applicability domain. By constructing comprehensive negative samples via a randomly chosen approach or other computational methods, recent studies have begun to overcome this drawback . The generated negative samples would inevitably contain potential cocrystals that have not been observed, which might affect the accuracy of the predictive models.…”
Section: Discussionmentioning
confidence: 99%
“…Graph convolutional neural networks do this by using graph convolutional layers, which can process node information passing through edges by combining linear and nonlinear transformations and pooling. , Finally, the corresponding features of the molecules will be extracted by the readout layer and generated as a one-dimensional sequence, which is further processed by the neural network to give the final output. In this research, the GCNs is built based on the model structure and hyperparameters reported by Devogelaer in 2020 . Five GCN were randomly trained on training datasets and further ensembled together to finally judge whether a cocrystal is formed.…”
Section: Machine Learning Modelingmentioning
confidence: 99%
“…Devogelaer and his colleagues also collected a positive dataset from CSD and constructed a dummy negative dataset using their own algorithm. They then ensembled a graph convolutional network (GCN) based on atomic features and an ECFP-based neural network (FPNN) as the cocrystal screening model and finally obtained about 80% accuracy and one new cocrystal …”
Section: Introductionmentioning
confidence: 99%
“…The method can be used as a preliminary screening tool for excluding the possible formation of immiscible solid states. Devogelaer et al 35 introduced two neural network models that accept a pair of molecules as input and classify whether they can form a cocrystal. Two models differed in their input molecular representations and initial preprocessing steps.…”
Section: Ai and Cocrystalmentioning
confidence: 99%